A Survey on Various Security Issues and Challenges to Secure Cloud Computing (International Journal of Innovative Research in Computer Science & Technology, 2018)
Cloud computing has evolved as one of the  most powerful approach in the IT industry. It provides  so many advantages like minimum expense, great  performance, availability of resources, due to which it is  considered as revolution amongst organizations. In  cloud computing various resources are shared through  network in open environment so that the user can access  the information from anywhere, but there exist the  issues of security and privacy of user and its  information. It also provides a broad study on the issues  and challenges of security .Growth of cloud computing  is mainly decreased due to these concerns and  challenges. Even though there is secure Homomorphic  encryption there lays certain security issues and attacks  with it. This paper deals with the analysis of security  issues on cloud computing and finding counter  measures on those issues. The fundamental security  issues such as confidentiality, integrity, availability,  trust and audit and compliance is analyzed and the  impact on each characteristics of cloud computing as  well as the third party control has been examined.
Keywords: Cloud Computing; Security Issues; Homomorphic encryption; Counter measure